A Quantitative Estimate of the Expected Shortening of the Median Isolation Period of Patients With COVID-19 After the Adoption of a Symptom-Based Strategy - Bai, Francesca; Tavelli, Alessandro; Mulè, Giovanni; Falcinella, Camilla; Mondatore, Debora; Tesoro, Daniele; Barbanotti, Diletta; Tomasoni, Daniele; Castoldi, Roberto; Augello, Matteo; Allegrini, Marina; Tagliaferri, Gianmarco; et al. (Frontiers in Public Health, 2021)
A long period of isolation was observed in patients hospitalized for COVID-19 in Milan over March-September 2020 (45; IQR: 37-54 days). A significantly shorter period would have been observed by the application of May-WHO (22, IQR 17-30 days, p<0.001) and October-Italian (26, IQR 21-34 days, p<0.001) Guidelines. The adoption of the new symptom-based criteria is likely to lead to a significant reduction in the length of the isolation period with potential social, economic and psychological benefits, particularly in the younger population with mild/moderate disease and no comorbidities.